Mente, mundo e significado: a dicotomia entre internismo e externismo. - Oliveira, Bruno Fernandes de (2016)
This dissertation aims to introduce and investigate the problem of meaning in the sphere of semantic externalism, propose by Hilary Putnam, and the internalist criticism of John Searle. Such proposal aims to show Putnam’s contribution in favor of the externalism and the internalist theory developed by Searle. The discussion that will be developed looks for the relation between the human mind and the world, in which the externalism defends a causal external relation as essential for the determination of meaning, whereas the internalism defends that the intentionality does not depend of a relation with the social/physical world in order to form a meaning. According to Searle, the meaning, the conscience, the intentionality and the states of mind are biological processes of the mind, therefore, any explanation about these states of mind should explain how the mind’s organism relates with reality. In The Meaning of “meaning”, Putnam presents her thesis of the semantic externalism and critics the individualism. The main goal is to basically refute the theories that supports that the states of mind and meaning of words are electrochemical processes of the mind, and as such, do not depend of the external world. With the objective of refuting the externalist theory, Searle develops the theory of intentionality as a solution for the most discussed problems in the history of philosophy, such as the theory of meaning, reference and mind-body problem. According to Searle, the intentionality does not require a relation with the social/physical world to form a meaning. Summarizing it, the internalist theory of Searle seeks to show that the world is not necessary in order to men attribute meaning to terms. However, the argument presented by the philosopher that meaning is nothing but a biological property of the brain leaves the issue language versus world to be explained.